Effects of Human Resource Management Practices on Corporate Entrepreneurship at a State Agency in South Africa - Aluwani Nthangeni; Marcia Lebambo (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
Organisations face rapid changes brought about by economic, political, social and technological changes. These changes compel organisations to review their business strategies and turn to CE as an ultimate source of competitive advantage. Furthermore, the human resource management (HRM) function is crucial in formulating competencies and supporting organisations in achieving their strategic objectives. This study sought to determine the effects of HRM practices on CE at a South African state-owned agency. The study adopted a qualitative single case study design using semi-structured interviews through Microsoft Teams. A purposive sample of nine top management and human resources employees participated in the study. The interviews were recorded and subsequently analysed using ATLAS.ti 23. The study shows that three HRM practices, namely, recruitment and selection, training and development, and performance appraisal, positively affect the adoption of CE at the North West Development Corporation (NWDC) in South Africa. The study provides practical guidance on how state agencies can effectively invest and promote entrepreneurial behaviour for optimal performance. The study contributes to the body of knowledge by proposing a revised conceptual framework for increasing CE in HRM systems for internal innovation performance by incorporating HRM practices. This framework includes HRM practices such as job design, recruitment, training, performance appraisal, and compensation. Furthermore, the study introduces organisational development as a strategic contributor to the successful implementation of this framework.